2011
DOI: 10.1109/tmag.2010.2072915
|View full text |Cite
|
Sign up to set email alerts
|

Micromagnetic Simulations of Vortex Resonances in Coupled Nanodisks

Abstract: The high-frequency response of two magnetostatically coupled nanodisks supporting a vortex state within a stack has been investigated by means of 3-D dynamic micromagnetic simulations performed in the frequency domain. These spectra reveal one or two resonance lines according to the vortex polarizations and chiralities. These sub-gigahertz resonance modes are associated with vortex core modes. The magnetostatic coupling controlled by the interdisk distance affects both the structure of the vortex core modes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
2
2
0
Order By: Relevance
“…3 ) of the fundamental vortex mode varying the dot thickness L are in a very good agreement with the experimental data, demonstrating the similar maximum of the dependence ω 0 ( L ). From the other side, our simulations are in qualitative agreement with the simulations by Boust et al 21 22 for the dots of small radius R = 80 nm. This allows us to consider the conducted micromagnetic simulations as a reliable tool to study in details the observed vortex excitation modes in thick dots.…”
Section: Resultssupporting
confidence: 90%
“…3 ) of the fundamental vortex mode varying the dot thickness L are in a very good agreement with the experimental data, demonstrating the similar maximum of the dependence ω 0 ( L ). From the other side, our simulations are in qualitative agreement with the simulations by Boust et al 21 22 for the dots of small radius R = 80 nm. This allows us to consider the conducted micromagnetic simulations as a reliable tool to study in details the observed vortex excitation modes in thick dots.…”
Section: Resultssupporting
confidence: 90%
“…In agreement with Ref. [32] the case of equal circularities provokes a larger static displacement of the cores. Depending on the geometry of the disks, the displacement is expected to emerge for the case of different circularities as well.…”
Section: Theoretical Model and Discussionsupporting
confidence: 91%
“…Stacking the vortices allows for a strongly increased packing density and has thus stimulated recent studies [23][24][25][26][27][28][29][30]. While for two-dimensional arrangements the minimization of the stray fields at the side surfaces creates the vortices and mediates their interaction, we observe a second coupling mechanism for three-dimensional stacks that has been investigated theoretically [26,31,32]. Due to core coupling the collective motions in an elementary stack of two vortices become a two-body problem.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation